2010
DOI: 10.54207/bsmps1000-2010-n61ea6
|View full text |Cite
|
Sign up to set email alerts
|

Study of floristic composition in alpine area of Kedarnath of Garhwal Himalaya in relation to density of Nardostachys jatamansi DC.

Abstract: The present study was undertaken to understand the community behaviour of Nardostachys jatamansi in three different sub sites viz., maximum, moderate and minimum density levels in the alpine areas of Kedarnath region of Rudraprayag district in Uttarakhand. The results reveal that the density was highest in the maximum sub site followed by in the moderate and minimum sub sites. Analysis of vegetation revealed that between different densities the community composition did not vary much. Although between various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In their study, Abies pindrow, Betula alnoides, Quercus semecarpifolia and Rhododendron campanulatum were common species on all four altitudinal gradients. Gargya et al [61], in their study in the central Himalaya in the alpine and sub-alpine regions, found similar results for the distribution of tree seedlings. At 3300 m altitude at the Yamnotri-Uttarkashi site, seedlings of Pyrus.…”
Section: Natural Forestsmentioning
confidence: 60%
“…In their study, Abies pindrow, Betula alnoides, Quercus semecarpifolia and Rhododendron campanulatum were common species on all four altitudinal gradients. Gargya et al [61], in their study in the central Himalaya in the alpine and sub-alpine regions, found similar results for the distribution of tree seedlings. At 3300 m altitude at the Yamnotri-Uttarkashi site, seedlings of Pyrus.…”
Section: Natural Forestsmentioning
confidence: 60%